(untitled) (Novateur Publications, 2025)
In today’s rapidly globalizing world, the need for digital transformation across all sectors has become more critical than ever. The digital economy, which encompasses the integration of digital technologies into all aspects of business and society, is reshaping traditional economic structures, including productivity and employment dynamics. OECD countries, which are at the forefront of economic development and technological innovation, provide valuable case studies of how digitalization affects economic growth and labor markets.